Navigating through the bulls and bears on the web : balancing information literacy skills and self-efficacy - Ang, Boren (2014)
Young investors increasingly turn to the Internet for financial information. Literature shows that individuals’ use of information is dependent on their levels of information literacy, among other factors. This paper analyses the empirical components of information literacy skills (recognising, searching, evaluating, and using) and self-efficacy in information use through a cross-sectional study of young investors in Singapore. Their information literacy and self-efficacy levels were also analysed across various income groups, gender and investing experience. This study fills in the literature gap by assessing the relative importance of each predictor variable on using quality financial information online. The sample of the study comprises of 346 young investors aged 18 to 27. A factor analysis uncovered four dimensions of information literacy in relation to stock market information: addressing information needs, evaluation skills, self-efficacy and search skills. A hierarchical multiple regression analysis along with the control variables (household income, financial literacy and digital skills) showed information literacy skills and self-efficacy to be significant predictors of quality financial information use. Young investors were found to rely more on self-efficacy than their search and evaluation skills when using quality financial information online. This study thus proposes a balance of high information literacy skills and a strong sense of self-efficacy.